Hide and run: Arginine-based endoplasmic-reticulum-sorting motifs in the assembly of heteromultimeric membrane proteins - Michelsen, Kai (2005)
Arginine-based endoplasmic reticulum (ER)-localization signals are sorting motifs that are involved in the biosynthetic transport of multimeric membrane proteins. After their discovery in the invariant chain of the major histocompatibility complex class II, several hallmarks of these signals have emerged. They occur in polytopic membrane proteins that are subunits of membrane protein complexes; the presence of the signal maintains improperly assembled subunits in the ER by retention or retrieval until it is masked as a result of heteromultimeric assembly. A distinct consensus sequence and their position independence with respect to the distal termini of the protein distinguish them from other ER-sorting motifs. Recognition by the coatomer (COPI) vesicle coat explains ER retrieval. Often, di-leucine endocytic signals occur close to arginine-based signals. Recruitment of 14-3-3 family or PDZ-domain proteins can counteract ER-localization activity, as can phosphorylation. This, and the occurrence of arginine-based signals in alternatively spliced regions, implicates them in the regulated surface expression of multimeric membrane proteins in addition to their function in quality control.